Land reform in South Africa as a means to combat poverty - Smit, MDJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
Right from the start the government’s aim through land reform was linked to economic growth and the alleviation of poverty. However, after ten years of democracy there are complaints that the delivery on land reform has not been entirely satisfactory. Recently quite a serious accusation came from some South African churches indicating that government has moved away from a pro-poor land reform agenda towards the support of a new upcoming class of black commercial farmers. Some observers want government to end the concentration of landownership in the hands of a minority, and to provide land to the poor. In this paper we argue that the maintenance of a viable agricultural sector on the one hand and making provision for the poor on the other, should not be regarded as opposing options. The successful development of black commercial farming could become in the medium and long run a significant means of poverty alleviation itself.